Lactic Acid Bacteria Antimicrobial Compounds: Characteristics and Applications - Reis, J. A. [UNESP]; Paula, A. T. [UNESP]; Casarotti, S. N. [UNESP]; Penna, A. L. B. [UNESP] (Springer, 2012)
The interest on novel biological preservation methods has been increasing during recent years, supported by research indicating that antagonistic microorganisms and their antimicrobial metabolites may have some potential use as natural preservatives as a way not only to control the growth but also to inactivate undesired microorganisms in food. Biopreservation using lactic acid bacteria (LAB) and/or their antimicrobial metabolites represents an alternative for improving food safety. These antimicrobial properties of LAB were derived from competition for nutrients and the production of one or more antimicrobial active metabolites such as organic acids (mainly lactic and acetic acid), hydrogen peroxide and also other compounds, such as bacteriocins and antifungal peptides. The important contribution of probiotic LAB in food preservation has been attracting much attention because of the nutritional qualities of the raw material through an extended shelf life of food and their ability to inhibit spoilage and foodborne pathogens, which is interesting for the food industry. In this review, we compiled the available data on the commonly used preservative and present the current knowledge regarding the antimicrobial compounds, especially bacteriocins, the mechanisms of the action and recent applications of antimicrobial compounds in food. The use of competitive microbiota as a biotechnological tool for food preservation may lead to improve the optimization and quality assurance of food products while at the same time retaining the sensory qualities of the product such as color, flavor, texture and nutritional value.
Keywords: Natural antimicrobials; Food safety; Food preservation; Bacteriocins; Hurdle technology; Shelf life